INVENTORY TURNOVER AND FIRM PERFORMANCE OF QUOTED CONSUMER GOODS MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
The study examined the relationship between inventory turnover and firm performance of quoted consumer goods manufacturing firms in Nigeria. Inventory management is critical to the success of manufacturing organisations in today’s ompetitive and dynamic business environment. The study specifically examined the relationship between inventory turnover period and two firm performance proxies; the net profit margin and operating cash flow to sales ratio. The study adopted the ex-post facto research design. The population of the study comprised quoted consumer goods manufacturing firms and the sample was delimited to this sector. The study relied on secondary data obtained from annual reports and accounts. The data were analysed using multiple regression technique. The results showed a non-significant negative relationship between inventory turnover period and net profit margin; secondly, a non[1]significant negative relationship between inventory turnover period and operating cash flow to sales ratio. Based on these, the study recommends amongst others that managers establish deliberate strategies for efficient inventory management; practices such as Demand Forecasting, Just in Time, and Vendor Management Inventory proven to positively impact organizational performance are recommended to ensure a sustainable increase in firm performance.
Keywords: Inventory Turnover Period; Net Profit Margin; Operating Cashflow to Sales Ratio; Firm Performance